Las redes anticomunistas entre América latina y Asia (1954-1980) - Ernesto Bohoslavsky (Les Cahiers de Framespa)
This article studies the relationships established between South and Central American and Asian anti-Communist organizations and military dictatorships between 1954 and 1980. Not only did some of these initiatives from Asian and Latin American dictatorships and rightist organizations elude the potential interest and control of the United States government, but they were directly opposed to it. Their first connections were established during four Anti-Communist conferences held in Latin American cities in the Fifties. The links between the Confederación Interamericana de Defensa del Continente and the Asian People’s Anti-Communist League paved the way for a lasting Asian-Latin American Anti-communist cooperation in the Sixties and even more so in the Seventies—a period when Taiwanese, Central and South American anti-communist dictatorships reinforced the ties between them in order to gain legitimacy in the face of increasing allegations of human rights violations and reduced international diplomatic recognition. This Asian-Latin American alliance was strengthened when the US government began to oppose these anti-Communist regimes.